2015
DOI: 10.1016/j.neuron.2014.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Distribution of Presynaptic Ca2+ Channels and Its Impact on Vesicular Release during Development

Abstract: SummarySynaptic efficacy and precision are influenced by the coupling of voltage-gated Ca2+ channels (VGCCs) to vesicles. But because the topography of VGCCs and their proximity to vesicles is unknown, a quantitative understanding of the determinants of vesicular release at nanometer scale is lacking. To investigate this, we combined freeze-fracture replica immunogold labeling of Cav2.1 channels, local [Ca2+] imaging, and patch pipette perfusion of EGTA at the calyx of Held. Between postnatal day 7 and 21, VGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
368
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(406 citation statements)
references
References 59 publications
32
368
1
5
Order By: Relevance
“…S5), consistent with estimates at the calyx of Held (20, 33), indicating that fixed buffers are present at >300 µM concentration in cMFBs (calculated from κ E = 15 and K D > 20 µM; Fig. S5).…”
Section: Discussionsupporting
confidence: 83%
“…S5), consistent with estimates at the calyx of Held (20, 33), indicating that fixed buffers are present at >300 µM concentration in cMFBs (calculated from κ E = 15 and K D > 20 µM; Fig. S5).…”
Section: Discussionsupporting
confidence: 83%
“…Finally, the finding of a decrease in release probability is consistent with previous results at several types of central synapses (47)(48)(49)(50); but see 32). In the calyx of Held this decrease is associated with a shortening of the AP waveform (51) and a consequent decrease of Ca 2+ entry (34). Second, a similar sharpening occurs at the level of VGCCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a large body of literature paints a more complex picture of the relationship of Ca 2+ channels and exocytotic sites. Functional measurements, largely relying on measurements of kinetics of Ca 2+ buffering, have revealed that different synapses use very different strategies for Ca 2+ -secretion coupling, with distances between Ca 2+ source and sensor that range from 10 nm to >100 nm (Bucurenciu et al, 2008; Eggermann et al, 2011; Keller et al, 2015; Nakamura et al, 2015). Similarly, at Schaffer collateral synapses, a variable arrangement between Ca 2+ channels and releasable vesicles may account for release properties, suggesting that direct molecular tethers between Ca 2+ channels and vesicles may not be required at all (Scimemi and Diamond, 2012), or at least not for all vesicles.…”
Section: Relevant Structures and Their Patterning In The Three Synaptmentioning
confidence: 99%